High and Ultra-high Performance Concretes: A Solution to Reinforced Concrete Durability under Harsh Climate of Arabian Gulf - Sohail, Muazzam Ghous; Kahraman, Ramazan; Al Nuaimi, Nasser; Alnahhal, Wael; Wasee, Muhammad (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Reinforced concrete (RC) infrastructure in the Arabian Gulf region deteriorates under severe environmental conditions after only short service life. To overcome this problem, it is imperative to employ high-quality concretes and reinforce them with rebars that are corrosion resistant. This paper investigates the durability performance of newly developed high performance concretes (HPC) and ultra-high performance concretes (UHPC). The HPC and UHPC were manufactured using locally available materials in Qatar without employing any special treatment. The durability characteristics of HPC and UHPC in comparison to a normal strength concrete (NSC) were determined. Durability indicators such as concrete resistivity, sorptivity, porosity and resistance to chloride permeability were evaluated in order to access the durability of these concretes. These parameters were also compared to the concrete core samples taken from 30 to 50 years old RC structures in Doha city. The electrical resistivity of HPC and UHPC was 11 and 20 times higher than NSC, respectively. Sorptivity was 2 and 3 times less than NSC, respectively for HPC and UHPC. While the porosity of HPC and UHPC was 2.45 and 1.43% respectively. These newly fabricated concretes showed higher performance in durability testing than the concretes from real structures. With such attributes, the UHPC will be a useful tool in arresting the rapid deterioration of RC structures especially under harsh-climatic conditions of the Arabian Gulf.